Alleviating student loneliness through mindful podcasts: An experimental study - Taufiqurrohman, Mhd. Soleh; Khoirot, Umdatul; El Fahmi, Elok Fa'iz Fatma (UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the effectiveness of the Mindful Podcast program in reducing loneliness among university students identified as experiencing mobile phone addiction. Using a quasi-experimental one-group pretest–posttest design, the intervention involved 10 participants who were selected through a screening process using the Mobile Phone Addiction Index (MPAI) and the R-UCLA Loneliness Scale. The Mindful Podcast program integrates mindfulness principles into an audio-based self-help format, delivered over eight 20-minute sessions (160 minutes total). Data were analyzed using repeated measures ANOVA to assess changes in loneliness across three measurement points: pretest, posttest, and two-week follow-up. The results showed a significant reduction in loneliness following the intervention (F = 116.169, p .001), with a large effect size (ω² = 0.651). Post hoc comparisons also indicated a strong and sustained reduction, with Cohen’s d values above 2.8. These findings suggest that the Mindful Podcast program is not only statistically effective but also practically valuable as a low-barrier, time-efficient, and accessible intervention for addressing loneliness in digitally dependent students. This study expands the application of mindfulness therapy into immersive audio media, proposing podcasts as active therapeutic tools rather than mere delivery platforms. Practically, universities and mental health practitioners can adopt podcast-based interventions as scalable and screen-free alternatives for promoting student mental well-being, especially where access to conventional face-to-face services is limited. KEY WORDS: loneliness; mobile phone addict; mindfulness; mindful podcast Copyright ©2025. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0